Prise en charge de la sécurité dans les petites entreprises manufacturières : état de la situation et pistes pour l’intervention et la recherche - Danièle Champoux; Jean-Pierre Brun (Perspectives Interdisciplinaires sur le Travail et la Santé)
Occupational health and safety (OHS) in small size enterprises (SSE’s) of less than 50 workers has therefore received little attention in Quebec in terms of either research or intervention and support to prevention. Estimation of OHS risks indicate SSE’s have serious problems aggravated by a limited access to human, economic and technological resources. It is now recognized strategies developed for large enterprises cannot be transferred to SSE’s. An exploratory study based on interviews with employers presents an overview of characteristic OHS representations and practices in SSE’s. Results will contribute to a first evaluation of their needs and will orient interventions as well as future research.